Lack of association between PAX6/SOSTDC1/FAM20B gene polymorphisms and mesiodens - Shanshan Liu; Jiancheng Li; Jincheng Xu; Shengkai Liao; Yongfeng Chen; Rongxiu Zhang; Ruixue Tian; Kai Zhang (BMC, 2019)
Abstract Background The purpose of this study was to analyze the association between the genetic polymorphism of genes (PAX6, SOSTDC1and FAM20B) and the susceptibility to mesiodens. Methods This study was carried out on 50 patients with mesiodens and 50 controls. The family history of each patient with mesiodens were recorded. Genomic DNA was extracted from saliva samples, and single nucleotide polymorphisms were detected in all exons and exon/intron boundaries of PAX6, SOSTDC1 and FAM20B using Sanger sequencing. The data were analyzed using pearson chi-square test with theoretical frequency ≥ 5. For theoretical frequency less than 5 but at least 1 (≤20% cell), the data were analyzed by continuity correction. For the rest, Fisher's Exact test was used. A P-value< 0.05 was considered statistically significant. The Odds ratio (OR) and confidence intervals (CI) were recorded. Results Three polymorphisms were detected in PAX6. Two polymorphisms were detected in SOSTDC1. Twenty-nine polymorphisms were detected in FAM20B. Although, the T allele of FAM20B (rs3766626) appears to be associated with mesiodens (P = 0.051), there were no significant differences of PAX6/SOSTDC1/FAM20B gene polymorphisms between the two groups. The T allele of FAM20B (rs3766626) was associated with susceptibility to two mesiodens (P < 0.001; OR = 8.333; CI = 2.516-27.600). Conclusions Lack of association between PAX6/SOSTDC1/FAM20B gene polymorphisms and mesiodens in the population studied was detected. Further studies with large samples on T allele of FAM20B (rs3766626) are needed.